Barriers to using electronic evidence based literature in nursing practice: a systematised review. (20th July 2017) - Sadoughi, Farahnaz; Azadi, Tania; Azadi, Tannaz
Abstract: Background: Nurses' use of electronic literature has remained limited. Objectives: The aim of this study was to identify barriers concerning application of electronic literature on evidence based practice in nursing. Methods: Six bibliographic databases were searched using the following keywords: challenges, barriers, obstacles, evidence based practice, EBP, information seeking, online databases, electronic literature, bibliographic databases and nurs*. Results were filtered to peer reviewed empirical studies, written in English or Persian and published from 2010 to 2017. Studies were selected based on specified inclusion criteria, and quality of the included studies was assessed. The approved articles ( n = 21) were extracted and synthesised. Discussion: There are different types of barriers in using electronic evidence based literature in nursing demonstrating the issue as a multi‐faceted problem. Not having enough time to conduct a search was the first major barrier noted by almost 81% ( n = 17) of the reviewed studies followed by lack of knowledge on searching skills (66%; n = 14) and access requirements (38%; n = 8). Conclusions: There appears to be an important role for hospital management in providing nurses with enough time and access to online information while at work and also for health care librarians together with nursing leaders in providing the required training on using electronic evidence based literature.